NeoTRACK trial: neoadjuvant TiRagolumab, Atezolizumab and Chemotherapy : dissection of IO- efficacy in NSCLC by longitudinal tracKing : protocol of a non-randomised, open-label, single-arm, phase II study - Rösch, Romina M.; Schnorbach, Johannes; Klotz, Laura Valentina; Griffo, Raffaella; Thomas, Michael; Stenzinger, Albrecht; Christopoulos, Petros; Allgäuer, Michael; Schneider, Marc; Schuler, Martin; Wiesweg, Marcel; Schramm, Alexander; et al. (BMJ open, 2025)
Background Immunotherapies targeting the programmed death receptor-1/programmed death ligand-1(PD-1/PD-L1) checkpoint have a major impact on the treatment of both resectable and advanced non-small cell lung cancer (NSCLC). Additional blockade of the T-cell immunoreceptor with immunoglobulin and immunoreceptor tyrosine-based inhibition motif domain (TIGIT)-receptor may synergistically foster the immune-related response. Several trials are currently investigating the combination of neoadjuvant platinum-based chemotherapy and dual checkpoint inhibition prior to curative surgery. The investigator-initiated NeoTRACK trial (EU CT number: 2022-501322-38-00; ClinicalTrials.gov identifier: NCT05825625; IKF056) aims to evaluate the feasibility and safety of perioperative anti-PD-L1 (by atezolizumab) and anti-TIGIT (by tiragolumab) treatment in combination with chemotherapy in patients with early stage NSCLC. - Methods and analysis NeoTRACK is an open-label, single-arm, prospective, bicentric phase II trial. Patients with NSCLC in clinical stages II, IIIA and IIIB (only T3N2) will receive two cycles of standard platinum-based chemotherapy in combination with the anti-TIGIT antibody tiragolumab and the anti-PD-L1 antibody atezolizumab, followed by curative surgery. After surgery, patients without pathological complete response (pCR) will receive another two cycles of chemotherapy in combination with tiragolumab and atezolizumab, followed by tiragolumab/atezolizumab maintenance for up to 1 year (maximum 16 cycles). Patients with pCR will only receive dual immunotherapy. All patients will be followed-up for 30 months after the last study treatment. The clinical study will be aligned with a translational research programme to investigate treatment-naïve tumour tissues, surgical specimens and longitudinally collected blood samples. 35 patients are planned for enrolment. Patient recruitment started in August 2023, and treatment of the last patient is estimated to start 2.5 years thereafter. - Discussion The NeoTRACK trial aims to assess the feasibility and efficacy of combining tiragolumab and atezolizumab as both neoadjuvant and adjuvant therapies in patients with resectable NSCLC. The concept of treatment personalisation based on postoperative pCR is of great clinical interest. - Ethics and dissemination The trial obtained ethical and regulatory approval in Germany through the Clinical Trials Information System (CTIS, ID: 2022-501322-38-00) and the Paul Ehrlich Institute (PEI, competent authority for approval of clinical trials using medicinal products for human use in Germany, process number: PB00148) on 30 March 2023. A data safety and monitoring board will meet regularly to review ongoing treatment in terms of safety.Study results will be published in peer-reviewed journals, presented at conferences and in the public registry of CTIS, following trial completion. - Trial registration number NCT05825625.